Pengaruh Komponen Arus Kas, Laba Perusahaan dan Return On Assets terhadap Harga Saham pada Perusahaan Manufaktur (Consumer Goods) yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2016 - Kadek Suputra Dana; A.A. Sri Purnami; Ni Putu Rediatni Giri (Warmadewa Economic Development Journal (WEDJ), 2018)
This research aims is to analyze the effect of the cash flow component, profit, and return on assets to the company`s price stock. This research using five independent variables such as cash flow operation, cash flow investation, cash flow budgeting, profit, and return on assets. While dependent variable is price stock. This research using purposive sampling method to collect data and secondary data from 23 companies which is used for sample. Multiple regression analyze has been used in this research and do some classic assumption test (normality test, multicollinearity test, heteroscedasticity test, and autocorellation test). The result shows that cash flow operation, cash flow investation,and profit have no significant effect to price stock. While cash flow budgeting and return on assets have positive and significant effect to price stock.